NITROGEN RATES ON GROWTH, YIELD AND NITRATE FOLIAR CONTENT OF ARUGULA - Soares Silva, Paulo Henrique [UNESP]; Cecilio Filho, Arthur Bernardes [UNESP]; Reis, Isaias dos Santos [UNESP]; Rugeles Reyes, Sergio Manuel [UNESP]; Pessoa Da Cruz, Mara Cristina [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2021)
Nitrogen is the second nutrient most demanded by arugula. However, the positive effect it has on yield can negatively impact the quality of this vegetable, with negative effects on human health. Two experiments (summer and autumn) were carried out to evaluate the effect of N rates (0, 50, 100, 150, 200 and 250 kg ha(-1)) on the arugula growth, yield and quality (nitrate content). Each experiment was set up in a randomized block design with four replications. Increasing rates of N reflected positively on leaf N content and thus, higher and desirable values of height, leaf number, leaf area and plant dry mass were obtained in both growing seasons. Consequently, the yield had significant increase, which N was maximized in summer (4.9 kg m(-2)) and autumn (2.6 kg m(-2)) and leaf N of 29.4 and 27.0 g kg(-1), respectively, at rates of 250 and 213 kg ha(-1) and both growing seasons. The higher rate the higher foliar nitrate content of arugula, in summer (2931.3 mg kg(-1)) and autumn (4218.4 mg kg(-1)). The foliar nitrate content in both crop season do not reach the risk level to human being heath.
Keywords: Eruca sativa Mill; Leaf vegetable; Nitrate; Quality